Analisis Perubahan Persepsi Jamaah Dakwah Ustadz Evie Effendi Di Kota Bandung - Nadhillah Kusindriani; Martha Tri Lestari (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung, 2019)
Ustadz Evie Effendi was a public figure who is known by the public as a modern ustadz that use the Sundanese language when do Da’wah. The perceptions given by the society particularly of ustadz Evie Effendi Da'wah pilgrims are positive until ultimately ustadz Evie exposed